Control Fundamentals with LabVIEW - Torres Chávez, Ivaldo; Mejía Bugallo, Diego Armando; Guadrón Guerrero, Oscar Eduardo (2025)
Fundamentals of Control with LabVIEW is an academic work that integrates the principles of automatic control theory with practical implementation in the LabVIEW graphical development environment, making use of the Control Design & Simulation Toolbox. Over the course of nine chapters, it presents a thematic progression that spans from the mathematical modeling of dynamic systems using transfer functions and state-space representation, to the design and analysis of feedback control systems in both time and frequency domains. The book provides tools for the simulation, visualization, and implementation of classical control algorithms, including stability criteria such as Routh-Hurwitz, root locus plotting, and frequency domain analysis using Bode, Nyquist, and Nichols diagrams.The didactic structure of the text is supported by functional examples and case studies that enable the development of skills in modeling, stability analysis, controller design, and performance evaluation of SISO systems. It emphasizes the inclusion of interactive exercises developed in LabVIEW, focused on the manipulation of state variables, synthesis of closed-loop systems, and comparison of reduced-order models. This work is intended for undergraduate and graduate engineering students, educators, researchers, and professionals seeking a solid and applied methodological approach to control system design, with an emphasis on visual simulation environments, thus facilitating the transition from abstract theory to practical implementation in real-world engineering contexts.
Keywords: Automatic control; LabVIEW; Mathematical modeling; System stability; Interactive simulation